Examining the influence of attachment styles on the gay individual's same-sex romantic relationships an in-depth analysis - Daria, Charlene Jean; Gabonada, Niño Angelo; Perez, Camilla Rochel; Sadian-Cercado, Ruth Edisel Rylle B.; Umil, Ysabelle
This qualitative study aimed to examine how attachment styles influence the relationship dynamics among gay couples and the challenges they encountered in their relationship. Using purposive sampling, this study involved 10 participants with varying attachment styles and are currently in a romantic same-sex relationship. The study revealed that attachment styles impact relationship dynamics in terms of trust, consistency, stability and mutual support,compromise, and need for intimacy. The findings also showed that challenges in the relationships related to insecurity, meeting expectations, and navigating time and attention between partners and family, were common among all attachment styles.